Molecular Dynamics at Extended Timescales. Issue 8 (20th August 2014) - Elber, Ron; Cardenas, Alfredo E.
Abstract The use of short time trajectory fragments to enhance sampling of kinetics is discussed. It is argued that partitioning of phase space with interfaces that are called milestones and conducting a large number of short time trajectories between these interfaces is a highly efficient and accurate method to calculate thermodynamics and kinetics. The method of Milestoning, which is a theory and an algorithm, enables the rapid calculations of fluxes, stationary distributions, and moments of the mean first passage time. It is based on sub‐nanosecond trajectories between cell partitions (milestones) that are defined in coarse space. While the method was applied in the past to highly complex systems, we illustrate it here on a pedagogical two‐dimensional system using dividers of Voronoi cells as milestones.